Performance evaluation of task scheduling algorithms in virtual cloud environment to minimize makespan - Kaur, Rajbhupinder; Laxmi, Vijay; Balkrishan (International journal of information technology (Singapore. Online), 2022)
Cloud computing has emerged as a foremost technology utilizing the notion of commercial application of technology with public users. Cloud computing is recognized because of its ability to dynamically allocate resources on-demand offering pronounced scalability, performance, minimal maintenance, and cost-effectiveness. The resources are shared among users via the virtualization technique. High performance can be extracted from cloud computing by effectively performing task scheduling. Task scheduling is the primary concern to be considered for the dynamic allocation of resources to enhance performance and minimize the makespan. Task scheduling is considered a major factor because it directly influences the other factors monitoring performance like power consumption, best cost, scalability, and availability. The research work is conducted to calculate the makespan in cloud computing via a virtual environment on four prominent task scheduling algorithms: FCFS (first come first serve), RR (round Robin), SJF (shortest job first), and PSO (particle swarm intelligence). The VMs (virtual machines) and data centers with unique ids have been brought into practice to analyze the working of considered task scheduling algorithms. The execution time required for the successful completion of each stage has been recorded to compute the makespan. The research paper discusses the adopted process used in executing the task scheduling via an appropriate algorithm, pseudocode, and flowchart. The results have been obtained based on the working principle of four task scheduling algorithms and compared based on makespan.